2009
DOI: 10.1080/01635580802419756
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Plant Foods and Associated Nutrients in Prostate Cancer Risk

Abstract: Plant foods and associated nutrients may impact prostate cancer (PC) risk and survival. Therefore, we compared dietary intake, mainly plant food groups among 382 controls and 478 PC cases (373 incident and 105 prevalent cases). Caucasian controls had significantly higher daily servings of vegetables (3.4 vs. 2.5, P= 0.002) and fruits and/or fruit juices (1.6 vs. 1.3, P = 0.02) compared to African American controls. In Caucasians, incident cases reported lower intake of fiber, vitamin C, vitamin A, alpha -carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
0
56
2
2
Order By: Relevance
“…Indeed, individuals with a higher LCHP score in our study had a lower intake of simple carbohydrates (as referred to sucrose intake, Table 2). Although a positive association of total protein intake and prostate cancer has been proposed (35), most studies do not support an association between total protein intake and prostate Downloaded by [Michigan State University] at 09:46 06 February 2015 Adjusted for energy intake (n = 566). c Adjusted for energy intake, smoking, regular physical activity, and level of education (n = 541).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, individuals with a higher LCHP score in our study had a lower intake of simple carbohydrates (as referred to sucrose intake, Table 2). Although a positive association of total protein intake and prostate cancer has been proposed (35), most studies do not support an association between total protein intake and prostate Downloaded by [Michigan State University] at 09:46 06 February 2015 Adjusted for energy intake (n = 566). c Adjusted for energy intake, smoking, regular physical activity, and level of education (n = 541).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a xenograft model showed that the low-carbohydrate diet could reduce tumor growth of prostate cancer and significantly prolong survival (8). Based on the above findings, several observational studies have investigated the association between dietary carbohydrate and prostate cancer risk, and the results are inconsistent (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Some studies conducted in the United States and Japan showed no relation between carbohydrate intake and prostate cancer (9)(10)(11); however, a significant association between carbohydrate intake and prostate cancer was found in a Chinese case-control study (13).…”
Section: Introductionmentioning
confidence: 95%
“…There are many interventions that involve modified test foods such as WGs with added fiber which are not to be confused with regular WG intake (Liatis et al, 2009). Some studies also report all grains that are not separated into refined and WGs (Lewis et al, 2009;Deneo-Pellegrini et al, 1999). These are not considered as WG unless the intake for only WGs can be isolated from RGs.…”
Section: Whole-grain Consumption and Interventionsmentioning
confidence: 99%
“…There are also a few studies that involve modified test foods such as added fiber these are not to be confused with normal WG intake and should be excluded. Some studies also report WGs as "grains" when this may imply both RGs and WGs (Lewis et al, 2009;Deneo-Pellegrini et al, 1999). These studies should be excluded unless WG consumption can be isolated from RGs.…”
Section: Types Of Interventionsmentioning
confidence: 99%